Hydrolysis of Methionine- and Histidine-Containing Peptides Promoted by Dinuclear Platinum(II) Complexes with Benzodiazines as Bridging Ligands: Influence of Ligand Structure on the Catalytic Ability of Platinum(II) Complexes - Snežana Rajković; Beata Warżajtis; Marija D. Živković; Biljana Đ. Glišić; Urszula Rychlewska; Miloš I. Djuran (Bioinorganic Chemistry and Applications)
Dinuclear platinum(II) complexes, [{Pt(en)Cl}2(μ-qx)]Cl2·2H2O (1), [{Pt(en)Cl}2(μ-qz)](ClO4)2 (2), and [{Pt(en)Cl}2(μ-phtz)]Cl2·4H2O (3), were synthesized and characterized by different spectroscopic techniques. The crystal structure of 1 was determined by single-crystal X-ray diffraction analysis, while the DFT M06-2X method was applied in order to optimize the structures of 1–3. The chlorido Pt(II) complexes 1–3 were converted into the corresponding aqua species 1a–3a, and their reactions with an equimolar amount of Ac–L–Met–Gly and Ac–L–His–Gly dipeptides were studied by 1H NMR spectroscopy in the pH range 2.0 < pH < 2.5 at 37°C. It was found that, in all investigated reactions with the Ac–L–Met–Gly dipeptide, the cleavage of the Met–Gly amide bond had occurred, but complexes 2a and 3a showed lower catalytic activity than 1a. However, in the reactions with Ac–L–His–Gly dipeptide, the hydrolysis of the amide bond involving the carboxylic group of histidine was observed only with complex 1a. The observed disparity in the catalytic activity of these complexes is thought to be due to different relative positioning of nitrogen atoms in the bridging qx, qz, and phtz ligands and consequent variation in the intramolecular separation of the two platinum(II) metal centers.